On the pathogenesis of angina pectoris and its silence. - James, T. N. (American Clinical and Climatological Association, 1989)
Recent interest in silent angina deals in a sense with a double unknown since the pathogenesis of angina pectoris remains unexplained. In this report, we present evidence from two human postmortem studies and from experiments conducted in eleven awake dogs which supports a hypothesis that angina pectoris may be mediated by an intracardiac chemoreceptor receiving its primary blood supply from the proximal coronary circulation. The clinical events and the postmortem findings in both human subjects supported the hypothesis. The somatic responses observed in the awake dogs resembled those of humans with angina pectoris. Because the cardiogenic hypertensive chemoreflex in dogs is maximally elicited by serotonin normally carried by the platelets and released during their aggregation, angina pectoris as well as numerous other clinical events observed during acute myocardial ischemic episodes could be similarly explained as consequences of the activation of a coronary chemoreceptor in man. Thus, at least some and possibly most examples of angina pectoris may be mediated via the coronary chemoreceptor and vagal afferents to the brain, and injury or destruction of this chemoreceptor could interdict the perception of anginal pain.